The iterative decoding algorithm research of Turbo Product Codes - Fu-Gang Wang; Yi Tang; Fan Yang (2010 International Conference on Apperceiving Computing and Intelligence Analysis, 2010)
This article has researched encoding and decoding algorithms of Turbo Product Codes focusing on analysis of Chase-Pyndiah algorithm-based soft in/soft out (SISO) iterative decoding algorithm. The algorithm simulation done under matlab7.0 environment shows that, on an AWGN channel using BPSK modulation, Turbo Product Codes do a similar decoding performance as Turbo codes with a simpler decoding method and faster convergence. After several iterations, the decoding performance of Turbo Product Codes, which can be regarded as a kind of excellent channel coding pattern, has been significantly improved. Finally, a further research on modified decoding algorithm, that is gradient decoding algorithm, has been done and the simulation result approves that it offers a very good compromise between complexity and performance.